2010
DOI: 10.1186/1471-2458-10-247
|View full text |Cite
|
Sign up to set email alerts
|

My partner wants a child: A cross-sectional study of the determinants of the desire for children among mutually disclosed sero-discordant couples receiving care in Uganda

Abstract: BackgroundThe percentages of couples in HIV sero-discordant relationships range from 5 to 31% in the various countries of Africa. Given the importance of procreation and the lack of assisted reproduction to avoid partner transmission, members of these couples are faced with a serious dilemma even after the challenge of disclosing their HIV status to their spouses. Identifying the determinants of the decision to have children among sero-discordant couples will help in setting reproductive intervention prioritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
175
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(193 citation statements)
references
References 30 publications
(45 reference statements)
13
175
5
Order By: Relevance
“…21,[33][34][35][36] In this exploratory study, the majority of couples without children desired to have children, supporting the findings of other studies regarding the desire for children among people living with HIV. 33,[37][38][39][40][41] An Ethiopian study of 460 HIV-positive individuals reported strong associations between parity, age, marriage or current relationship, and the desire to have children. 41 A survey among 114 mutually disclosed sero-discordant couples in Kampala, Uganda found that 59% desired to have children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,[33][34][35][36] In this exploratory study, the majority of couples without children desired to have children, supporting the findings of other studies regarding the desire for children among people living with HIV. 33,[37][38][39][40][41] An Ethiopian study of 460 HIV-positive individuals reported strong associations between parity, age, marriage or current relationship, and the desire to have children. 41 A survey among 114 mutually disclosed sero-discordant couples in Kampala, Uganda found that 59% desired to have children.…”
Section: Discussionmentioning
confidence: 99%
“…41 A survey among 114 mutually disclosed sero-discordant couples in Kampala, Uganda found that 59% desired to have children. 37 Factors influencing fertility desire included the belief that their partner wanted children, young age, relatives' expectations and knowledge of treatment effectiveness. 37 Similar to other studies 33,39 our study shows that reproductive intentions of discordant couples are shaped by complex personal, interpersonal, medical and health care factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV transmission risk in patients on HAART is low only if the following conditions are met: the HIV-infected patient is receiving HAART with excellent adherence; patients disclose their HIV status and inquire about HIV status of their sexual partners; the viral load is consistently undetectable for a long time; and no sexually transmitted infections (STIs) are present in either partners. The above conditions are not met in many sub-Saharan African settings, as many studies [56][57][58][59][60][61] report that sub-optimal adherence, high fertility intentions, and risk factors for acquisition of STI (such as multiple sexual partners, and inconsistent condom use) are common. In many settings in sub-Saharan Africa, such as eastern and southern Africa, high-risk behaviors occur in HIV patients before and after initiating HAART [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…The provision of this care has led to a decrease in morbidity and mortality among HIV-positive patients [1]. It is therefore hypothesized that the improved quality of life could lead to increased fertility among HIV-positive women [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%